1993
DOI: 10.1007/bf00735923
|View full text |Cite
|
Sign up to set email alerts
|

Cellular pharmacokinetics of doxorubicin in patients with chronic lymphocytic leukemia: comparison of bolus administration and continuous infusion

Abstract: The purpose of this study was to determine whether administration of doxorubicin (DOX) as a continuous infusion or a bolus injection resulted in similar leukemic cell drug concentration in patients with refractory chronic lymphocytic leukemia (CLL). This study was carried out on five patients with refractory CLL, with DOX administered either as a bolus injection (35 mg/m2; CHOP protocol) or as a constant-rate infusion for a period of 96 h (9 mg/m2 per day; VAD protocol). The two types of drug administration we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…In addition to these reports our findings show that cleavage of caspases and PARP following drug treatment and g-irradiation involves activation of the CD95 system. Drug concentrations used in this study correspond to plasma levels which can be achieved in patients following chemotherapy (Muller et al, 1993;Dominici et al, 1989) indicating that our findings may be of therapeutical relevance. We previously identified stimulation of the CD95 system as one mechanism leading to apoptosis in leukemia and neuroblastoma cells in response to drug treatment (Friesen et al, 1996;Fulda et al, 1997).…”
Section: A Bsupporting
confidence: 66%
“…In addition to these reports our findings show that cleavage of caspases and PARP following drug treatment and g-irradiation involves activation of the CD95 system. Drug concentrations used in this study correspond to plasma levels which can be achieved in patients following chemotherapy (Muller et al, 1993;Dominici et al, 1989) indicating that our findings may be of therapeutical relevance. We previously identified stimulation of the CD95 system as one mechanism leading to apoptosis in leukemia and neuroblastoma cells in response to drug treatment (Friesen et al, 1996;Fulda et al, 1997).…”
Section: A Bsupporting
confidence: 66%
“…Importantly, we demonstrated that doxorubicin and, to a greater extent, daunorubicin induced detrimental responses in the endothelium at clinically relevant concentrations. Indeed, the plasma concentrations of ALL patients have been determined to range from 20 nM to 2 lM for doxorubicin and 20 nM-10 lM for Daunorubicin depending on the route of drug administration (Kokenberg et al, 1988;Muller et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…S9788 (6-4-[2,2-di(4-fluorophenyl)ethylamino]piperidinl-yl N,N'-dipropen-2-yl 1,3,5-triazine 2,4-diamine, bismethanesulphonate) was synthesised at the Servier Research Institute (Courbevoie, France (Lucas et al, 1993) or VRP (Ozols et al, 1987;Cairo et al, 1989 (10, 20, 30 and 60 min). Cells were washed twice in ice-cold phosphate-buffered saline (PBS), trypsinised, and the cell-associated drug concentrations were determined by high-performance liquid chromatography (HPLC) with fluorimetric detection after sonication and extraction by organic solvent as described elsewhere (Muller et al, 1993 washed, trypsinised and counted as previously described. Efflux at each time point was determined by the method described in the section on DOX accumulation.…”
Section: Methodsmentioning
confidence: 99%